Sociolinguistics of the Korean Wave Hallyu and Soft Power - Samosir, Nora (Taylor & Francis, 2024)
Samosir and Wee examine how the immensely popular Korean Wave (""K-wave"") also known as Hallyu is wielded as soft power through the use of communication for persuasion and attraction on the global stage. The Korean Wave refers to the global spread and popularity of South Korean culture, particularly its pop music (""K-pop""), serialised dramas (""K-dramas"") and films (""K-films""). Given the South Korean government's involvement in providing funding and publicity, the Korean Wave raises interesting sociolinguistic questions about the relationship between artistry and citizenship, the use of social media in facilitating the consumption of cultural products, and, ultimately, the nature of soft power itself. Studies of soft power have tended to come from the field of international relations. This book shows that sociolinguistics actually has a number of tools in its conceptual arsenal - such as indexicality, stance taking, affect, and styling - that can shed light on the Korean Wave as a form of soft power. As the first book-length sociolinguistic analysis of the Korean Wave and soft power, this book demonstrates how K-pop, K-dramas, and K-films have been able to encourage in consumers an anthropological stance towards all things Korean. This volume will be of particular interest to students and scholars in sociolinguistics, political science, cultural studies, and Korean studies.